2013
DOI: 10.1192/bjp.bp.112.111195
|View full text |Cite
|
Sign up to set email alerts
|

Adjusted prognostic association of depression following myocardial infarction with mortality and cardiovascular events: individual patient data meta-analysis

Abstract: BackgroundThe association between depression after myocardial infarction and increased risk of mortality and cardiac morbidity may be due to cardiac disease severity.AimsTo combine original data from studies on the association between post-infarction depression and prognosis into one database, and to investigate to what extent such depression predicts prognosis independently of disease severity.MethodAn individual patient data meta-analysis of studies was conducted using multilevel, multivariable Cox regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
146
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(166 citation statements)
references
References 93 publications
9
146
1
3
Order By: Relevance
“…The finding that pertinent cardiovascular disease indices such as LVEF did not mediate the depression-prognosis link fits with some recent findings (Meijer et al, 2013a) which show only partial mediation of the depressionprognosis link when analysing various disease indices. The lack of mediation here may be explained by the depression scales used in the present study, which omitted somatic items, and these items may be more related to disease indices than other items (de Miranda Azevedo et al, 2014).…”
Section: Tale 4 About Here Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The finding that pertinent cardiovascular disease indices such as LVEF did not mediate the depression-prognosis link fits with some recent findings (Meijer et al, 2013a) which show only partial mediation of the depressionprognosis link when analysing various disease indices. The lack of mediation here may be explained by the depression scales used in the present study, which omitted somatic items, and these items may be more related to disease indices than other items (de Miranda Azevedo et al, 2014).…”
Section: Tale 4 About Here Discussionsupporting
confidence: 72%
“…As noted, the relationship between theoretical vulnerabilities, depressive symptoms and trajectories, and outcomes has been examined previously (Doyle et al, 2011b;Kaptein et al, 2006;Martens et al, 2008;Rieckmann et al, 2006), but not all simultaneously. It is perhaps not surprising that depressive trajectories were strongly predictive of outcome, given the well-established association between depression and mortality in coronary patients (Meijer et al, 2013a). However, what is new in this study is the fact that both depression trajectories -subthreshold and persistent -were associated with increased risk of poorer outcomes.…”
Section: Tale 4 About Here Discussionmentioning
confidence: 35%
See 1 more Smart Citation
“…In a previous analysis, we found that depression was not a stronger risk factor for post-MI mortality than for other causes combined during a 24-month follow-up [8]. A meta-analysis in 2004 [2] reported that post-MI depression is associated with a 2-to 2.5-fold increased risk of impaired cardiovascular outcome, and a recent meta-analysis in 2013 indicated that, although the association between depression following MI and prognosis is attenuated after adjustment for cardiac disease severity, depression remains independently associated with prognosis with a 22% increased risk of all-cause mortality and a 13% increased risk of cardiovascular events per standard deviation in depression z-score [25]. The relation of depression with cardiac mortality or all-cause mortality was more significant in the older studies (OR 3.22 before 1992) than in the more recent studies (OR 2.01 after 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Depression in particular is common among cardiac patients, with a prevalence ranging between 20 and 30%, which is roughly ten times higher than in the general population (Thombs et al, 2006;Myers et al, 2012). Depressed CAD patients are at increased risk of rehospitalization (Myers et al, 2012;Damen et al, 2013) and the risk of all-cause mortality is two-fold higher in depressed CAD patients (Smolderen et al, 2009;Meijer et al, 2013Meijer et al, , 2011. Furthermore, depressed patients tend to have a worse general treatment adherence (e.g., Swardfager et al, 2011;Rieckmann et al, 2006a).…”
Section: Introductionmentioning
confidence: 98%